Preparation method of kovar alloy foil
By strictly controlling the content of trace element S and increasing dehydrogenation in the preparation process of Kval alloy foil, the problems of difficult control of trace element and hydrogen embrittlement in the prior art are solved, and the high toughness and ductility of the alloy are achieved. Extend service life.
Patent Information
- Application Number
- CN202411557633.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-04
AI Technical Summary
In the existing Kova alloy foil preparation process, it is difficult to control the content of trace elements, especially harmful trace elements such as sulfur, which is difficult to effectively reduce, resulting in the alloy being prone to hydrogen embrittlement problems, affecting performance and service life.
By strictly controlling the mass percentage of trace element S in the raw materials of coval alloy (S≤0.01%), and adding a dehydrogenation process during the preparation process, the hydrogen in the alloy is removed, the harmful effects of sulfur are reduced, and the hydrogen embrittlement problem is avoided.
Accurate control of trace elements is achieved, the hydrogen content in the alloy is reduced, the toughness and ductility of the foil is improved, the service life is extended, and the uniformity of the tissue is improved.
Smart Images

Figure CN119433364A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of Kovar alloy foil preparation, and in particular to a method for preparing Kovar alloy foil. Background Art
[0002] Kovar alloy, as a special alloy material with excellent performance, is widely used in the fields of electronics, aviation, aerospace and precision instruments, especially in the occasions that require high stability and low expansion coefficient. With the advancement of science and technology and the deepening of application, higher requirements are put forward for the performance and preparation process of Kovar alloy foil, especially in terms of thickness uniformity, component purity and microstructure of foil.
[0003] The existing preparation methods of Kovar alloy foil often face many challenges, such as imprecise composition control, poor uniformity of structure due to simple ingot casting and forging processes, and easy generation of internal stress and impurity residues during sintering. These directly affect the performance and service life of the final product. In particular, the control of the content of trace elements in the preparation process is crucial to improving the overall performance of the alloy. However, it is unrealistic to completely eliminate some harmful trace elements in the preparation process of Kovar alloy. Taking sulfur (S) as an example, too high a sulfur content will lead to a significant decrease in the corrosion resistance and mechanical properties of the alloy. Moreover, according to research It is shown that even a very small amount of S in Kovar alloy may cause hydrogen embrittlement in Kovar alloy. This is because the presence of S will promote the metal's ability to absorb hydrogen, allowing more hydrogen atoms to enter the interior of the metal. In addition, since S reduces the ductility and toughness of the metal, the material is more likely to break when affected by hydrogen embrittlement. At the same time, S may also promote the diffusion and aggregation of hydrogen atoms in the metal, thereby aggravating the occurrence of hydrogen embrittlement. Therefore, how to control the content of trace elements in the preparation process of Kovar alloy and how to further reduce harmful trace elements is a difficult problem faced by this field.
[0004] In view of this, the art needs a new method for preparing Kovar alloy foil to solve the above problems. Summary of the invention
[0005] In order to solve the above technical problems, that is, to solve the problems in the prior art that it is difficult to control the content of trace elements in the preparation process of Kovar alloy foil and it is difficult to further reduce the harmful trace elements, the present invention provides a method for preparing Kovar alloy foil, which aims to accurately control the content of trace elements in the preparation process of Kovar alloy foil, and can further reduce the content of harmful trace elements such as sulfur, avoid hydrogen embrittlement of Kovar alloy, and improve the ductility and toughness of Kovar alloy.
[0006] The present invention provides a method for preparing a kovar alloy foil, the preparation method comprising:
[0007] S1: placing a kovar alloy raw material in a smelting furnace for smelting, and pouring the smelted molten metal into a target mold to form a steel ingot, wherein the mass percentage of the trace element S component in the kovar alloy raw material is controlled to be: S≤0.01%;
[0008] S2: heating the steel ingot prepared in step S1 and forging it into a blank;
[0009] S3: Cooling the blank forged in step S2 and then cleaning its surface;
[0010] S4: performing a dehydrogenation treatment on the blank after the surface cleaning in step S3;
[0011] S5: The alloy after the dehydrogenation treatment in step S4 is subjected to one hot rolling treatment and multiple cold rolling treatments to obtain a Kovar alloy foil of target thickness.
[0012] In certain preferred embodiments, the composition of the kovar alloy raw material includes, by mass percentage: C≤0.015%, P≤0.01%, S≤0.01%, Mn: 0.35-0.45%, Si≤0.20%, Cu≤0.10%, Cr≤0.10%, Mo≤0.10%, Ni: 28.8%-29.2%, Co: 17.0-17.3%, Zr: 0.1-0.2%, Nb: 0.05-0.15%, and the balance is Fe.
[0013] In certain preferred embodiments, the melting temperature is 1600-1700°C, and the melting is carried out under an argon protective atmosphere; before pouring, the molten metal is kept in a vacuum environment of 10-50Pa for 10-15 minutes for preliminary vacuum treatment, and then argon is introduced into the molten metal for blowing and stirring, the argon flow rate is controlled at 5-10L / min, and the stirring time is 5-8 minutes; the pouring temperature is 1550-1600°C, and the pouring speed is 2-5kg / s; and the target mold is insulated during the pouring process.
[0014] In some preferred embodiments, step S2 specifically includes:
[0015] The steel ingot prepared in step S1 is heated, firstly the steel ingot is heated to 550-600°C at a heating rate of 60-80°C / h for preheating, and the heat preservation time is 2-3 hours, and then the temperature is increased to a forging temperature range of 1150-1200°C at a rate of 100-120°C / h, and during the heating process, the oxygen content in the furnace is controlled to be below 0.05% by a gas circulation device in the furnace;
[0016] The steel ingot is gradually forged into the required billet shape by using a multi-pass forging method with small deformation, and the deformation of each pass is controlled between 12% and 18%.
[0017] In some preferred embodiments, step S3 specifically includes:
[0018] Place the blank in a holding furnace and slowly cool it down with the furnace at a cooling rate of 60-80℃ / h;
[0019] The blank is polished by mechanical polishing, the polishing pressure is 0.2-0.4MPa, and the polishing speed is 10-15m / min;
[0020] The blank is placed in a chemical cleaning tank and cleaned with a cleaning solution for 15-25 minutes. During the cleaning process, the cleaning solution is stirred at a stirring speed of 30-50 r / min.
[0021] After cleaning, the blank is rinsed with clean water at a flushing pressure of 0.1-0.3MPa and a flushing time of 3-5 minutes.
[0022] In some preferred embodiments, step S4 specifically includes:
[0023] Placing the blank after surface cleaning in step S3 in a dehydrogenation furnace, and filling the dehydrogenation furnace with argon gas;
[0024] The alloy is heated and dehydrogenated in a dehydrogenation furnace, the dehydrogenation temperature is 1430-1480° C., and the dehydrogenation time is 2.5-3.5 hours;
[0025] After dehydrogenation is completed, the dehydrogenation furnace is turned off and the alloy is allowed to cool naturally to room temperature in the dehydrogenation furnace.
[0026] In some preferred embodiments, step S4 further comprises:
[0027] The alloy after dehydrogenation treatment is ground by a grinding machine, wherein the grinding direction remains unchanged;
[0028] The polishing machine is used to polish the alloy after grinding.
[0029] In some preferred embodiments, step S5 specifically includes:
[0030] The alloy after the dehydrogenation treatment in step S4 is hot rolled at a temperature of 410-430° C. for 70-80 minutes;
[0031] The hot-rolled alloy is subjected to multiple cold rolling, cleaning and annealing steps, wherein the annealing temperature after the first cold rolling is 470-480° C., the annealing time is 65-75 minutes, and the cleaning is carried out with dilute hydrochloric acid.
[0032] In certain preferred embodiments, the hot-rolled alloy is subjected to three cold rolling, cleaning and annealing steps, specifically:
[0033] The hot-rolled alloy is sent to a rolling mill for the first rolling, and the rolled alloy is washed with dilute hydrochloric acid and then annealed for the first time;
[0034] The alloy after the first annealing is sent to a rolling mill for a second rolling, and the rolled alloy is washed with dilute hydrochloric acid and then annealed for a second time, wherein the annealing temperature is 780-790°C and the annealing time is 60-70 minutes;
[0035] The alloy after the second annealing is sent to the rolling mill for the third rolling. The rolled alloy is washed with dilute hydrochloric acid and then annealed for the third time to obtain a Kovar alloy foil of target thickness, wherein the annealing temperature is 530-540°C and the annealing time is 60-70 minutes.
[0036] In some preferred embodiments, step S5 further comprises:
[0037] The Kovar alloy foil after the third annealing is cleaned with an ultrasonic cleaner for 10-15 minutes and then polished.
[0038] The present invention has the following beneficial effects:
[0039] The preparation method of the Kovar alloy foil provided by the present invention reduces the factors that may cause hydrogen embrittlement from the source by strictly controlling the mass percentage of trace element S in the Kovar alloy raw material (S≤0.01%), and adds a dehydrogenation treatment process in the preparation process to further remove the hydrogen that may exist in the alloy. After the dehydrogenation treatment, the hydrogen content in the alloy is greatly reduced, and the toughness and ductility of the foil are improved, so that it can better resist the action of external forces during use, and is not prone to hydrogen embrittlement fracture, which significantly prolongs the service life of the Kovar alloy foil. After the steel ingot is poured, forging treatment is performed to fully refine and homogenize the structure of the alloy, and subsequent hot rolling and multiple cold rolling treatments further improve the uniformity of the structure. The present invention does not require particularly high-precision smelting equipment and complex powder processing equipment, and ordinary smelting furnaces and forging equipment can meet production requirements after appropriate parameter adjustment and maintenance, which greatly reduces the cost of the equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] The features and advantages of the present invention will be more clearly understood by referring to the accompanying drawings, which are schematic and should not be construed as limiting the present invention in any way. In the accompanying drawings:
[0041] Figure 1 The present invention is a flow chart of the method for preparing the Kovar alloy foil. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0043] Based on the problems pointed out in the background technology that it is difficult to control the content of trace elements in the preparation process of Kovar alloy foil in the prior art and it is difficult to further reduce harmful trace elements, the present invention provides a method for preparing Kovar alloy foil, aiming to accurately control the content of trace elements in the preparation process of Kovar alloy foil, and to further reduce the content of harmful trace elements such as sulfur, avoid hydrogen embrittlement of Kovar alloy, and improve the ductility and toughness of Kovar alloy.
[0044] like Figure 1 As shown, the preparation method of the Kovar alloy foil provided by the present invention comprises:
[0045] S1: placing a kovar alloy raw material in a smelting furnace for smelting, and pouring the smelted molten metal into a target mold to form a steel ingot, wherein the mass percentage of the trace element S component in the kovar alloy raw material is controlled to be: S≤0.01%, preferably, the other components are as follows: C≤0.015%, P≤0.01%, Mn: 0.35-0.45%, Si≤0.20%, Cu≤0.10%, Cr≤0.10%, Mo≤0.10%, Ni: 28.8%-29.2%, Co: 17.0-17.3%, Zr: 0.1-0.2%, Nb: 0.05-0.15%, and the balance is Fe;
[0046] In the above, the manganese (Mn) content is controlled between 0.35-0.45%, so as to play the role of deoxidation and desulfurization, and can combine with sulfur to form high-melting-point manganese sulfide, reduce the harmful effects of sulfur, and improve the strength and hardness of the alloy without affecting the toughness of the alloy; the chromium (Cr) content is controlled to be ≤0.10%, chromium can improve the corrosion resistance and oxidation resistance of the Kovar alloy, at high temperatures, chromium can form a stable chromium oxide film to prevent further oxidation of the alloy; the molybdenum (Mo) content is controlled to be ≤0.10%, molybdenum can improve the strength and high-temperature performance of the Kovar alloy, it can be dissolved in the alloy matrix, enhance the interatomic bonding force of the alloy, thereby improving the strength and hardness of the alloy, and at the same time, molybdenum can also The recrystallization temperature of the alloy is increased so that it can still maintain good mechanical properties at high temperatures; the zirconium (Zr) content is controlled between 0.1-0.2%. Zirconium mainly plays the role of grain refinement in Kovar alloy. It can inhibit the grain growth of the alloy during solidification, making the alloy structure more uniform and dense, thereby improving the strength and toughness of the alloy. At the same time, zirconium can also improve the corrosion resistance of the alloy; the niobium (Nb) content is controlled between 0.05-0.15%. Niobium can improve the strength and corrosion resistance of Kovar alloy; it can form stable compounds with elements such as carbon and nitrogen to reduce the adverse effects of these elements on the properties of the alloy; at the same time, niobium can also refine the grains and improve the toughness and processing performance of the alloy.
[0047] In addition, the inventors found that the above-mentioned content of nickel (Ni) and cobalt (Co) can jointly form a stable austenite structure, so that the alloy has good toughness and plasticity at room temperature. Nickel expands the austenite phase region, and cobalt improves the thermal stability and strength of the alloy. The two cooperate with each other to enhance the comprehensive mechanical properties of the alloy. In a high temperature environment, this synergistic effect is more obvious, which can keep the alloy with good strength and hardness and is not easy to deform and soften. When the sulfur content of the above-mentioned manganese (Mn) and sulfur (S) is controlled at a low level (≤0.01%), manganese can combine with sulfur to form manganese sulfide with a high melting point, reduce the harmful effects of sulfur, and prevent the occurrence of hot brittleness. This synergistic effect helps to improve the mechanical properties and processing properties of the alloy and reduce the defects caused by sulfur. Zirconium (Zr) and niobium (Nb) can promote each other in grain refinement. Zirconium in the alloy can inhibit the growth of grains during solidification, make the structure more uniform and dense, and improve the strength and toughness of the alloy. Niobium forms stable compounds with elements such as carbon and nitrogen to reduce the adverse effects of these elements on the properties of the alloy. At the same time, it can also refine the grains. The two work together to further enhance the mechanical properties and processing properties of the alloy. In the subsequent forging and rolling process of the Kovar alloy, the refined grains can make the alloy easier to deform, improve the dimensional accuracy and surface quality. At the same time, the uniform and dense structure can also improve the corrosion resistance of the alloy and extend its service life.
[0048] Preferably, in the above step S1, the melting temperature is 1600-1700°C, and the melting is carried out under an argon protective atmosphere to prevent oxidation and air absorption of the alloy, so as to provide high-quality molten metal for subsequent processes; the mold is made of H13 steel, and the inner surface of the mold is finely ground and polished to make the surface roughness Ra between 0.8-1.6μm to ensure the smooth surface of the steel ingot and reduce stress concentration points during subsequent processing; a layer of high-temperature resistant release agent, such as boron nitride coating, is applied to the inner wall of the mold, and the coating thickness is controlled between 0.05-0.1mm, which can facilitate the demolding of the steel ingot and reduce the adhesion between the steel ingot and the mold, thereby reducing the possibility of surface defects; the smelted molten metal is fully degassed, and methods such as blowing stirring or vacuum treatment can be used. For example, the molten metal is first kept in a vacuum environment of 10-50Pa for 10-15 minutes for preliminary vacuum treatment, and then argon is introduced into the molten metal for blowing and stirring. The argon flow rate is controlled at 5-10L / min, and the stirring time is 5-8 minutes. The hydrogen content in the molten metal is reduced as much as possible to prevent the occurrence of hydrogen embrittlement; the pouring temperature is controlled within an appropriate range, generally slightly higher than the liquidus temperature of the alloy. For Kovar alloy, the pouring temperature is controlled between 1550-1600℃ to ensure that the molten metal has good The fluidity should be high, but not too high to cause aspiration and oxidation. The molten metal should flow smoothly into the mold during pouring. The bottom pouring method should be adopted, and the pouring speed should be controlled at 2-5kg / s to avoid splashing and turbulence, and to prevent the air and impurities from being drawn in. During the pouring process, the mold should be insulated, such as using insulation materials (such as aluminum silicate fiber) to wrap the outside of the mold. The thickness of the insulation layer should be controlled between 30-50mm to slow down the cooling speed of the ingot, make the internal structure of the ingot more uniform, and reduce the internal stress caused by uneven cooling.
[0049] S2: heating the steel ingot prepared in step S1 and forging it into a blank;
[0050] Preferably, the above step S2 specifically includes:
[0051] The steel ingot prepared in step S1 is heated, firstly the steel ingot is preheated to 550-600℃ at a heating rate of 60-80℃ / h, the holding time is 2-3 hours, and then the temperature is raised to the forging temperature range at a rate of 100-120℃ / h, and the forging heating temperature is controlled between 1150-1200℃; during the heating process, the atmosphere in the furnace is ensured to be uniform, and the oxygen content in the furnace is controlled below 0.05% by the gas circulation device in the furnace to prevent local oxidation or decarburization of the steel ingot; a multi-pass small deformation forging method is adopted to gradually forge the steel ingot into the desired blank shape; the deformation amount of each pass is controlled between 12%-18%, for example, rough forging is first performed to forge the shape of the steel ingot roughly into a shape close to the blank, the rough forging passes are 3-5 times, and then multiple fine forgings are performed, the fine forging passes are 1-2 times, and the fine forging passes are 1-3 times. For 5-8 times, the organization is gradually refined and the dimensional accuracy is improved; during the forging process, the forging direction and deformation sequence are controlled so that the blank can be fully deformed in different directions; for example, axial forging is performed first, and then radial forging is performed, and the reduction amount of each forging is controlled between 10-20mm to ensure that all parts of the blank can obtain a good forging effect; the striking force and frequency of the forging equipment are controlled. For large-volume blanks, a hydraulic press is used for forging, and the pressure of the hydraulic press is controlled between 100-150MPa; for small-volume blanks, a mechanical hammer is used for forging, and the striking force of the mechanical hammer is controlled between 500-800kN, and the striking frequency is controlled between 30-50 times / min to avoid excessive striking force causing internal cracks in the blank. At the same time, the appropriate frequency can ensure the smooth progress of the forging process;
[0052] S3: Cooling the blank forged in step S2 and then cleaning its surface;
[0053] Preferably, step S3 specifically includes:
[0054] After forging, the blank is cooled. Preferably, a slow cooling method is used, such as placing the blank in a heat preservation furnace and slowly cooling it with the furnace, and the cooling rate is controlled at about 60-80℃ / h, or wrapping the blank with heat preservation materials such as asbestos for cooling, and the thickness of the heat preservation materials is controlled between 20-30mm to reduce the cooling rate and reduce the residual stress and structural unevenness caused by excessive cooling; the surface is cleaned by a combination of mechanical grinding and chemical cleaning; first, a grinding wheel or a wire brush is used to perform preliminary grinding and removal of the oxide scale on the surface of the blank, and the grinding pressure is controlled between 0.2-0.4MPa and the grinding speed is 10-15m / min; then the blank is placed in a chemical cleaning tank For cleaning, the cleaning liquid is a solution containing an appropriate amount of acid and corrosion inhibitor, such as dilute hydrochloric acid (concentration of 8%-10%) or sulfuric acid solution (concentration of 6%-8%), and the amount of corrosion inhibitor added is 0.8%-1% of the mass of the acid solution; the cleaning time is determined according to the thickness of the oxide scale on the surface of the blank and the degree of contamination, generally 15-25 minutes; the cleaning liquid should be continuously stirred during the cleaning process, and the stirring speed is 30-50r / min to ensure uniform cleaning and prevent excessive corrosion of the surface of the blank; after cleaning, the blank is rinsed with clean water at a flushing pressure of 0.1-0.3MPa and a flushing time of 3-5 minutes to remove the residual cleaning liquid and impurities on the surface, and then dried at a drying temperature of 90-110℃. The time is 1.5-2 hours, ensuring that the surface of the blank is dry and clean, and preparing for subsequent flaw detection and processing procedures; a variety of flaw detection methods are used to conduct comprehensive inspections on the cleaned blanks to ensure the internal quality of the blanks; for example, first use an ultrasonic flaw detector to inspect the blanks to detect whether there are cracks, looseness and other defects inside the blanks; the frequency of ultrasonic flaw detection is selected according to the size and material of the blanks, generally between 2.5-4MHz; for large-volume blanks, multi-probe and multi-angle flaw detection is used, and the probe spacing is controlled between 50-80mm to ensure comprehensive detection coverage; then magnetic particle flaw detection is performed to detect tiny defects on the surface and near the surface of the blanks; after the blanks are magnetized, magnetic powder suspension is evenly sprayed on their surface Liquid, magnetic powder concentration is 10-20g / L, observe the aggregation of magnetic powder, and judge whether there are defects; when magnetic particle inspection, control the magnetization current and magnetic field strength within the appropriate range, the magnetization current is 500-800A, and the magnetic field strength is 2000-3000Gs to ensure the detection sensitivity; analyze and evaluate the defects found by flaw detection; if it is a small surface defect, when the defect size is less than 2mm, it is repaired by grinding, repair welding and other methods; if it is a large internal defect, the defect size is greater than 5mm or the defect depth exceeds 10% of the thickness of the blank, it is necessary to decide whether to scrap the blank according to the severity and location of the defect; the repaired part should be inspected again to ensure that the quality meets the requirements;
[0055] S4: performing a dehydrogenation treatment on the blank after the surface cleaning in step S3;
[0056] Preferably, step S4 specifically includes:
[0057] The blank after surface cleaning in step S3 is placed in a dehydrogenation furnace, and argon gas is filled into the dehydrogenation furnace; the dehydrogenation furnace is used to heat the alloy for dehydrogenation, the dehydrogenation temperature is 1430-1480°C, and the dehydrogenation time is 2.5-3.5 hours; after the dehydrogenation is completed, the power of the dehydrogenation furnace is turned off and the alloy is naturally cooled to room temperature in the dehydrogenation furnace; the alloy after dehydrogenation is ground by a grinder, wherein the grinding direction remains unchanged; the alloy after grounding is polished by a polisher;
[0058] S5: subjecting the alloy subjected to the dehydrogenation treatment in step S4 to a Kovar alloy foil having a target thickness by subjecting the alloy to a hot rolling treatment once and a cold rolling treatment multiple times;
[0059] Preferably, step S5 specifically includes:
[0060] The alloy after the dehydrogenation treatment in step S4 is hot rolled at a temperature of 410-430°C for 70-80 minutes, and the blank is further deformed by hot rolling to improve the structure and performance, and prepare for the subsequent cold rolling process; the alloy after hot rolling is subjected to multiple cold rolling, cleaning and annealing steps, wherein the annealing temperature after the first cold rolling is 470-480°C, the annealing time is 65-75 minutes, and the cleaning is carried out with dilute hydrochloric acid; it should be particularly noted that the texture in the alloy after hot rolling is transformed into a weaker random and diffuse texture, and the first rolling and annealing temperature is 470-480°C, the annealing time is 65-75 minutes, and the cleaning is carried out with dilute hydrochloric acid. The annealing parameter setting of 10 minutes is compared with the excessively high annealing temperature range (resulting in excessively large grain size, reducing the strength and hardness of the material) and the excessively low annealing temperature range (resulting in incomplete crystallization, the presence of dislocations and substructures, resulting in reduced plasticity, poor toughness, and increased crack extension) in the prior art. The plastic anisotropy of the final rolled sample obtained by the present invention is most significantly improved, and the plastic anisotropy index can be reduced to 11.9% at most. The texture is mainly a specific cubic texture variant with a crystal plane index of 100 and a crystal direction index of 110, which achieves the best in terms of comprehensive mechanical properties and anisotropy, and significantly reduces the plastic anisotropy while ensuring the strength of the material.
[0061] Specifically, the hot-rolled alloy undergoes three cold rolling, cleaning and annealing steps, specifically: the hot-rolled alloy is fed into a rolling mill for the first rolling, and the rolled alloy is cleaned with dilute hydrochloric acid and then subjected to the first annealing; the alloy after the first annealing is fed into a rolling mill for the second rolling, and the rolled alloy is cleaned with dilute hydrochloric acid and then subjected to the second annealing, wherein the annealing temperature is 780-790°C, and the annealing time is 60-70 minutes; the alloy after the second annealing is fed into a rolling mill for the third rolling, and the rolled alloy is cleaned with dilute hydrochloric acid and then subjected to the third annealing to obtain a kovar alloy foil of a target thickness, wherein the annealing temperature is 530-540°C, and the annealing time is 60-70 minutes; the kovar alloy foil after the third annealing is cleaned with an ultrasonic cleaner for 10-15 minutes, and then polished.
[0062] It should be noted that, after repeated experiments, analysis and comparison by the inventors, it was found that S has a certain surface activity in the alloy. When the S content is high (more than 0.01%), it will be highly enriched on the surface of the alloy liquid. During the smelting and pouring process, the alloy liquid is in contact with the surrounding atmosphere, and the presence of S will change the physical and chemical properties of the alloy liquid surface, making hydrogen more easily adsorbed on the alloy liquid surface. This may be because S atoms will form some weak chemical bonds or physical adsorption with hydrogen molecules, increasing the dissolution and adsorption probability of hydrogen in the alloy liquid. In contrast, when the S content is controlled below 0.01%, its enrichment on the alloy liquid surface is significantly reduced, and the alloy liquid surface's adsorption capacity for hydrogen is weakened. Thereby reducing the amount of hydrogen entering the alloy liquid; in addition, when the S content is high, it will affect the structure and properties of the oxide film on the surface of the alloy; during the high-temperature smelting process, the alloy will react with oxygen in the air to form an oxide film; the oxide film with a high S content may have more defects and pores, and these defects provide permeation channels for hydrogen; hydrogen can diffuse more easily into the alloy through these channels, resulting in an increase in the hydrogen content in the alloy; and when the S content is controlled at a lower level (below 0.01%), the oxide film formed is denser and more uniform, which can effectively block the penetration of hydrogen, reduce the possibility of hydrogen entering the alloy, and thus help control the hydrogen content of the alloy; in addition, in the subsequent removal of the alloy liquid During the degassing process, such as vacuum treatment and blowing and stirring, the presence of S will have an adverse effect on the degassing effect. For example, during vacuum treatment, S will form low-volatile compounds with other elements or impurities in the alloy. These compounds are not easy to evaporate and discharge in a vacuum environment, thus affecting the removal efficiency of hydrogen; and during the blowing and stirring process, S will react chemically with argon and consume part of the argon. At the same time, the generated products may be wrapped around the hydrogen bubbles, preventing the hydrogen bubbles from floating up and being discharged, resulting in poor degassing effect and ultimately a higher hydrogen content in the alloy; when the S content in the raw material is controlled below 0.01%, the interference factors are reduced during the degassing process; vacuum treatment can be more effective. The argon gas can effectively remove the hydrogen in the alloy liquid, because there are no excessive S-related compounds to hinder the volatilization of hydrogen; when blowing and stirring, the argon gas can contact the alloy liquid more smoothly, and take out the hydrogen dissolved in the alloy liquid, which improves the degassing efficiency and enables the hydrogen content in the alloy to be better controlled; in the subsequent processing such as forging and rolling, the atoms inside the alloy will move and rearrange; when the S content in the raw material is high, the alloy is more likely to produce stress concentration and micro defects during processing; these defective parts will become hydrogen gathering points, promoting the diffusion and aggregation of hydrogen; the accumulation of hydrogen at the defects may cause problems such as hydrogen embrittlement, further affecting the performance of the alloy; and when the S content is controlled at 0.When the S content is below 0.01%, the alloy has a more uniform structure during processing, fewer defects, and a correspondingly reduced hydrogen diffusion path; this makes the distribution of hydrogen inside the alloy more uniform, reduces the adverse effects caused by hydrogen aggregation, and is conducive to maintaining a low hydrogen content and good alloy properties; during the dehydrogenation process, the S content will also affect the dehydrogenation effect; when the S content exceeds 0.01%, it will react with the gas produced during the dehydrogenation process or other elements in the alloy to form some stable compounds, which may inhibit the removal of hydrogen; for example, S will form some stable hydrides with hydrogen inside the alloy, so that the dehydrogenation process requires higher temperatures and longer times to achieve the same dehydrogenation effect; on the contrary, when the S content is controlled below 0.01%, the dehydrogenation process is smoother; under the same dehydrogenation treatment conditions (such as dehydrogenation temperature and time), it can more effectively remove hydrogen from the alloy, reduce the hydrogen content to a lower level, and improve the quality and performance stability of Kovar alloy foil. .
[0063] The technical solution of the present invention is further described below in conjunction with a number of embodiments:
[0064] Embodiment 1
[0065] Prepare a raw material of Kovar alloy, the composition of the raw material of Kovar alloy is calculated by mass percentage: C = 0.015%, P = 0.01%, S = 0.01%, Mn = 0.35%, Si = 0.20%, Cu = 0.10%, Cr = 0.10%, Mo = 0.10%, Ni = 28.8%, Co = 17.0%, Zr = 0.1%, Nb = 0.05%, and the balance is Fe;
[0066] The Kovar alloy raw material is placed in a smelting furnace and smelted at 1600℃. Argon gas is used as a protective atmosphere during the smelting process. The mold is made of H13 steel, and the inner surface of the mold is finely ground and polished to make the surface roughness Ra reach 0.8μm. Boron nitride coating is applied to the inner wall of the mold with a coating thickness of 0.05mm. The smelted metal liquid is first kept in a vacuum environment of 10Pa for 10 minutes for preliminary vacuum treatment, and then argon gas is introduced into the metal liquid for blowing and stirring. The argon gas flow rate is controlled at 5L / min and the stirring time is 5 minutes. The pouring temperature is controlled at 1550℃, and the bottom pouring method is adopted. The pouring speed is controlled at 2kg / s. The outside of the mold is wrapped with aluminum silicate fiber, and the thickness of the insulation layer is controlled at 30mm.
[0067] The steel ingot is preheated to 550°C at a heating rate of 60°C / h, and the holding time is 2 hours. Then, the temperature is raised to 1150°C at a rate of 100°C / h for forging. The deformation amount of each pass is controlled at 12%. Rough forging is performed 3 times first, and then fine forging is performed 5 times. The forging equipment is a hydraulic press, and the pressure is controlled at 100MPa. During the forging process, axial forging is performed first, and the reduction amount of each forging is controlled at 10mm. Then radial forging is performed, and the reduction amount of each forging is controlled at 10mm. After forging, the blank is placed in a holding furnace and slowly cooled with the furnace. The cooling rate is controlled at 60°C / h.
[0068] First, the surface oxide scale of the blank was polished and removed with a grinding wheel, with a polishing pressure of 0.2MPa and a polishing speed of 10m / min; then the blank was placed in a chemical cleaning tank, the cleaning solution was dilute hydrochloric acid (concentration 8%), corrosion inhibitor (0.8% of the acid solution mass) was added, the cleaning time was 15 minutes, and the stirring speed during the cleaning process was 30r / min; after cleaning, it was rinsed with clean water, with a flushing pressure of 0.1MPa and a flushing time of 3 minutes, and finally dried at 90℃ for 1.5 hours; first, the blank was inspected with an ultrasonic flaw detector, and the ultrasonic The wave flaw detection frequency is 2.5MHz. For large-volume blanks, multi-probe and multi-angle flaw detection is adopted, and the probe spacing is controlled at 50mm; then magnetic particle flaw detection is carried out, the magnetic particle concentration is 10g / L, the magnetization current is 500A, and the magnetic field strength is 2000Gs; if tiny surface defects are found (defect size is less than 2mm), they are repaired by grinding; if large internal defects are found (defect size is greater than 5mm or defect depth exceeds 10% of the blank thickness), the blank is scrapped; the repaired part is tested again by flaw detection;
[0069] The cooled blank is placed in a dehydrogenation furnace, argon is filled into the dehydrogenation furnace, and the blank is heated to 1430°C for dehydrogenation treatment for 2.5 hours; after the dehydrogenation is completed, the blank is naturally cooled to room temperature with the furnace; the alloy after the dehydrogenation treatment is polished by a grinder, wherein the grinding direction remains unchanged; the alloy after the grinding treatment is polished by a polishing machine;
[0070] The alloy after dehydrogenation treatment was hot rolled at a temperature of 410°C and a time of 70 minutes; the alloy after hot rolling was cold rolled three times, cleaned and annealed; after the first cold rolling, annealed at 470°C for 65 minutes, and cleaned with dilute hydrochloric acid; after the second cold rolling, annealed at 780°C for 60 minutes; after the third cold rolling, annealed at 530°C for 60 minutes to obtain a Kovar alloy foil of target thickness; the foil after the third annealing was cleaned with an ultrasonic cleaner for 10 minutes and then polished.
[0071] Embodiment 2
[0072] Prepare a raw material of Kovar alloy, the composition of the raw material of Kovar alloy is calculated by mass percentage: C = 0.01%, P = 0.005%, S = 0.005%, Mn = 0.4%, Si = 0.15%, Cu = 0.08%, Cr = 0.08%, Mo = 0.08%, Ni = 29%, Co = 17.15%, Zr = 0.15%, Nb = 0.1%, and the balance is Fe;
[0073] The Kovar alloy raw material is placed in a melting furnace and melted at 1650℃. Argon gas is used as a protective atmosphere during the melting process. H13 steel is used for the mold, and the inner surface of the mold is finely ground and polished to make the surface roughness Ra reach 1.2μm. Boron nitride coating is applied to the inner wall of the mold, and the coating thickness is 0.08mm. The smelted metal liquid is first kept in a vacuum environment of 30Pa for 12 minutes for preliminary vacuum treatment, and then argon gas is introduced into the metal liquid for blowing and stirring. The argon gas flow rate is controlled at 8L / min, and the stirring time is 6 minutes. The pouring temperature is controlled at 1580℃, and the bottom pouring method is adopted. The pouring speed is controlled at 3kg / s; the outside of the mold is wrapped with aluminum silicate fiber, and the thickness of the insulation layer is controlled at 40mm.
[0074] The steel ingot is preheated at a heating rate of 70℃ / h to 580℃, and the holding time is 2.5 hours. Then, the temperature is raised to 1180℃ at a rate of 110℃ / h for forging. The deformation of each pass is controlled at 15%. Rough forging is performed 4 times first, and then fine forging is performed 6 times. The forging equipment is a hydraulic press, and the pressure is controlled at 120MPa. During the forging process, axial forging is performed first, and the reduction amount of each forging is controlled at 15mm, and then radial forging is performed, and the reduction amount of each forging is controlled at 15mm. After forging, the blank is wrapped with asbestos insulation material for cooling. The thickness of the insulation material is 25mm, and the cooling rate is controlled at 70℃ / h.
[0075] First, use a wire brush to grind and remove the oxide scale on the surface of the blank, with a grinding pressure of 0.3MPa and a grinding speed of 12m / min; then put the blank into a chemical cleaning tank, the cleaning solution is dilute sulfuric acid (concentration 7%), and a corrosion inhibitor is added (0.9% of the acid solution mass), the cleaning time is 20 minutes, and the stirring speed during the cleaning process is 40r / min; after cleaning, rinse with clean water, the flushing pressure is 0.2MPa, the flushing time is 4 minutes, and finally dry at 100℃ for 1.8 hours; first use an ultrasonic flaw detector to detect the blank, The frequency of ultrasonic flaw detection is 3MHz. For large-volume blanks, multi-probe and multi-angle flaw detection is adopted, and the probe spacing is controlled at 60mm. Then magnetic particle flaw detection is carried out, and the magnetic particle concentration is 15g / L, the magnetization current is 600A, and the magnetic field strength is 2500Gs. If a small surface defect is found (the defect size is less than 2mm), it is repaired by welding. If a large internal defect is found (the defect size is greater than 5mm or the defect depth exceeds 10% of the blank thickness), the blank is scrapped; the repaired part is tested again.
[0076] The cooled blank is placed in a dehydrogenation furnace, argon is filled into the dehydrogenation furnace, and the blank is heated to 1450°C for dehydrogenation treatment for 3 hours; after the dehydrogenation is completed, the blank is naturally cooled to room temperature with the furnace; a grinder is used to grind the alloy after the dehydrogenation treatment, and a cross-grinding method is used during the grinding (i.e., first grinding a certain number of times in one direction, and then grinding the same number of times in a vertical direction); a polisher is used to polish the alloy after the grinding treatment, and the polishing pressure and rotation speed are controlled within a suitable range during the polishing process;
[0077] The alloy after dehydrogenation treatment was hot rolled at a temperature of 420°C for 75 minutes; the alloy after hot rolling was cold rolled three times, cleaned and annealed; after the first cold rolling, annealing was performed at 475°C for 70 minutes, and cleaning was performed with dilute hydrochloric acid; after the second cold rolling, annealing was performed at 785°C for 65 minutes; after the third cold rolling, annealing was performed at 535°C for 65 minutes to obtain a Kovar alloy foil of target thickness; the foil after the third annealing was cleaned with an ultrasonic cleaner for 12 minutes and then polished.
[0078] Embodiment 3
[0079] Prepare a raw material of Kovar alloy, the composition of the raw material of Kovar alloy is calculated by mass percentage: C = 0.008%, P = 0.003%, S = 0.003%, Mn = 0.42%, Si = 0.12%, Cu = 0.06%, Cr = 0.06%, Mo = 0.06%, Ni = 29.1%, Co = 17.2%, Zr = 0.18%, Nb = 0.12%, and the balance is Fe;
[0080] The Kovar alloy raw material is placed in a melting furnace and melted at 1680°C. Argon gas is used as a protective atmosphere during the melting process. The mold is made of H13 steel, and the inner surface of the mold is finely ground and polished to make the surface roughness Ra reach 1.4μm. Boron nitride coating is applied to the inner wall of the mold, and the coating thickness is 0.09mm. The smelted metal liquid is first kept in a vacuum environment of 40Pa for 13 minutes for preliminary vacuum treatment, and then argon gas is introduced into the metal liquid for blowing and stirring. The argon gas flow rate is controlled at 9L / min, and the stirring time is 7 minutes. The pouring temperature is controlled at 1590°C, and the bottom pouring method is adopted. The pouring speed is controlled at 4kg / s; the outside of the mold is wrapped with aluminum silicate fiber, and the thickness of the insulation layer is controlled at 45mm.
[0081] The steel ingot is preheated to 590°C at a heating rate of 75°C / h, and the holding time is 2.8 hours. Then, the temperature is raised to 1190°C at a rate of 115°C / h for forging. The deformation of each pass is controlled at 16%. Rough forging is performed 4 times first, and then fine forging is performed 7 times. The forging equipment is a hydraulic press, and the pressure is controlled at 130MPa. During the forging process, axial forging is performed first, and the reduction amount of each forging is controlled at 18mm. Then radial forging is performed, and the reduction amount of each forging is controlled at 18mm. After forging, the blank is wrapped with asbestos insulation material for cooling. The thickness of the insulation material is 28mm, and the cooling rate is controlled at 75°C / h.
[0082] First, the oxide scale on the surface of the blank was polished and removed with a grinding wheel, with a polishing pressure of 0.35MPa and a polishing speed of 13m / min; then the blank was placed in a chemical cleaning tank, the cleaning solution was dilute hydrochloric acid (concentration 9%), corrosion inhibitor (0.95% of the acid mass) was added, the cleaning time was 22 minutes, and the stirring speed during the cleaning process was 45r / min; after cleaning, it was rinsed with clean water, with a flushing pressure of 0.25MPa and a flushing time of 4 minutes, and finally dried at 105℃ for 1.9 hours; first, the blank was inspected with an ultrasonic flaw detector, The frequency of ultrasonic flaw detection is 3.5MHz. For large-volume blanks, multi-probe and multi-angle flaw detection is adopted, and the probe spacing is controlled at 70mm. Then magnetic particle flaw detection is carried out, and the magnetic particle concentration is 18g / L, the magnetization current is 700A, and the magnetic field strength is 2800Gs. If tiny surface defects (defect size is less than 2mm) are found, they are repaired by grinding. If large internal defects are found (defect size is greater than 5mm or defect depth exceeds 10% of the blank thickness), the blank is scrapped; the repaired parts are tested again.
[0083] The cooled blank is placed in a dehydrogenation furnace, argon is filled into the dehydrogenation furnace, and the blank is heated to 1460°C for dehydrogenation treatment for 3.2 hours; after the dehydrogenation is completed, the blank is naturally cooled to room temperature with the furnace; a grinder is used to grind the alloy after the dehydrogenation treatment, and a spiral grinding path is used during grinding (grinding from the center to the outside in a spiral manner); a polisher is used to polish the alloy after the grinding treatment, and the polishing liquid is regularly replaced during the polishing process to ensure the polishing effect;
[0084] The alloy after dehydrogenation treatment was hot rolled at a temperature of 425°C and a time of 78 minutes; the alloy after hot rolling was cold rolled three times, cleaned and annealed; after the first cold rolling, it was annealed at 478°C for 72 minutes, and washed with dilute hydrochloric acid; after the second cold rolling, it was annealed at 788°C for 68 minutes; after the third cold rolling, it was annealed at 538°C for 68 minutes to obtain a Kovar alloy foil of target thickness; the foil after the third annealing was cleaned with an ultrasonic cleaner for 13 minutes and then polished.
[0085] Embodiment 4
[0086] Prepare a raw material of Kovar alloy, the composition of the raw material of Kovar alloy is calculated by mass percentage: C = 0.005%, P = 0.002%, S = 0.002%, Mn = 0.45%, Si = 0.1%, Cu = 0.05%, Cr = 0.05%, Mo = 0.05%, Ni = 29.2%, Co = 17.3%, Zr = 0.2%, Nb = 0.15%, and the balance is Fe;
[0087] The Kovar alloy raw material is placed in a smelting furnace and smelted at 1700℃. Argon gas is used as a protective atmosphere during the smelting process. H13 steel is used for the mold, and the inner surface of the mold is finely ground and polished to make the surface roughness Ra reach 1.6μm. Boron nitride coating is applied to the inner wall of the mold with a coating thickness of 0.1mm. The smelted metal liquid is first kept in a vacuum environment of 50Pa for 15 minutes for preliminary vacuum treatment, and then argon gas is introduced into the metal liquid for blowing and stirring. The argon gas flow rate is controlled at 10L / min and the stirring time is 8 minutes. The pouring temperature is controlled at 1600℃, and the bottom pouring method is adopted, and the pouring speed is controlled at 5kg / s. The outside of the mold is wrapped with aluminum silicate fiber, and the thickness of the insulation layer is controlled at 50mm.
[0088] The steel ingot is preheated to 600℃ at a heating rate of 80℃ / h, and the holding time is 3 hours, and then the temperature is raised to 1200℃ at a rate of 120℃ / h for forging; the deformation amount of each pass is controlled at 18%, and rough forging is performed 5 times first, and then fine forging is performed 8 times; the forging equipment is a hydraulic press, and the pressure is controlled at 150MPa; during the forging process, axial forging is first performed, and the reduction amount of each forging is controlled at 20mm, and then radial forging is performed, and the reduction amount of each forging is controlled at 20mm; after forging, the blank is placed in a holding furnace and slowly cooled with the furnace, and the cooling rate is controlled at 80℃ / h;
[0089] First, the surface oxide scale of the blank was polished and removed with a wire brush, with a polishing pressure of 0.4MPa and a polishing speed of 15m / min; then the blank was placed in a chemical cleaning tank, the cleaning solution was dilute sulfuric acid (concentration 8%), corrosion inhibitor (1% of the acid solution mass) was added, the cleaning time was 25 minutes, and the stirring speed during the cleaning process was 50r / min; after cleaning, it was rinsed with clean water, with a flushing pressure of 0.3MPa and a flushing time of 5 minutes, and finally dried at 110℃ for 2 hours; first, the blank was inspected with an ultrasonic flaw detector, and the ultrasonic flaw detector was used to inspect the blank. The wave flaw detection frequency is 4MHz. For large-volume blanks, multi-probe and multi-angle flaw detection is adopted, and the probe spacing is controlled at 80mm; then magnetic particle flaw detection is carried out, the magnetic particle concentration is 20g / L, the magnetization current is 800A, and the magnetic field strength is 3000Gs; if tiny surface defects are found (defect size is less than 2mm), they are repaired by welding; if large internal defects are found (defect size is greater than 5mm or defect depth exceeds 10% of the blank thickness), the blank is scrapped; the repaired part is tested again by flaw detection;
[0090] The cooled blank is placed in a dehydrogenation furnace, argon is filled into the dehydrogenation furnace, and the blank is heated to 1480°C for dehydrogenation treatment for 3.5 hours; after the dehydrogenation is completed, the blank is naturally cooled to room temperature with the furnace; the alloy after dehydrogenation treatment is polished by a grinder, and the surface of the blank is divided into several areas for grinding in sequence; the alloy after grinding treatment is polished by a polisher, and the polishing parameters are adjusted according to the surface conditions of the blank during the polishing process;
[0091] The alloy after dehydrogenation treatment was hot rolled at a temperature of 430°C for 80 minutes; the alloy after hot rolling was cold rolled three times, cleaned and annealed; after the first cold rolling, it was annealed at 480°C for 75 minutes, and washed with dilute hydrochloric acid; after the second cold rolling, it was annealed at 790°C for 70 minutes; after the third cold rolling, it was annealed at 540°C for 70 minutes to obtain a Kovar alloy foil of target thickness; the foil after the third annealing was cleaned with an ultrasonic cleaner for 15 minutes and then polished.
[0092] Embodiment 5
[0093] Prepare a raw material of Kovar alloy, the composition of the raw material of Kovar alloy is calculated by mass percentage: C = 0.012%, P = 0.008%, S = 0.008%, Mn = 0.38%, Si = 0.18%, Cu = 0.09%, Cr = 0.09%, Mo = 0.09%, Ni = 28.9%, Co = 17.1%, Zr = 0.12%, Nb = 0.08%, and the balance is Fe;
[0094] The Kovar alloy raw material is placed in a melting furnace and melted at 1630°C. Argon gas is used as a protective atmosphere during the melting process. The mold is made of H13 steel, and the inner surface of the mold is finely ground and polished to make the surface roughness Ra reach 1μm. Boron nitride coating is applied to the inner wall of the mold, and the coating thickness is 0.06mm. The smelted metal liquid is first kept in a vacuum environment of 20Pa for 11 minutes for preliminary vacuum treatment, and then argon gas is introduced into the metal liquid for blowing and stirring. The argon gas flow rate is controlled at 6L / min, and the stirring time is 6 minutes. The pouring temperature is controlled at 1560°C, and the bottom pouring method is adopted. The pouring speed is controlled at 3kg / s; the outside of the mold is wrapped with aluminum silicate fiber, and the thickness of the insulation layer is controlled at 35mm;
[0095] The steel ingot is preheated at a heating rate of 65°C / h to 560°C, and the holding time is 2.2 hours. Then, the temperature is raised to 1160°C at a rate of 105°C / h for forging. The deformation of each pass is controlled at 13%. Rough forging is performed 3 times, and then fine forging is performed 6 times. The forging equipment is a hydraulic press, and the pressure is controlled at 110MPa. During the forging process, axial forging is performed first, and the reduction amount of each forging is controlled at 12mm. Then radial forging is performed, and the reduction amount of each forging is controlled at 12mm. After forging, the blank is wrapped with asbestos insulation material for cooling. The thickness of the insulation material is 22mm, and the cooling rate is controlled at 65°C / h.
[0096] First, the oxide scale on the surface of the blank was polished and removed with a grinding wheel, with a polishing pressure of 0.25 MPa and a polishing speed of 11 m / min; then the blank was placed in a chemical cleaning tank, the cleaning solution was dilute hydrochloric acid (concentration 8.5%), corrosion inhibitor (0.85% of the acid mass) was added, the cleaning time was 18 minutes, and the stirring speed during the cleaning process was 35 r / min; after cleaning, it was rinsed with clean water, with a flushing pressure of 0.15 MPa and a flushing time of 3.5 minutes, and finally dried at 95°C for 1.6 hours; first, the blank was detected with an ultrasonic flaw detector The ultrasonic flaw detection frequency is 2.8MHz. For large-volume blanks, multi-probe and multi-angle flaw detection is adopted, and the probe spacing is controlled at 55mm; then magnetic particle flaw detection is carried out, and the magnetic particle concentration is 12g / L, the magnetization current is 550A, and the magnetic field strength is 2200Gs; if a small surface defect is found (the defect size is less than 2mm), it is repaired by grinding; if a large internal defect is found (the defect size is greater than 5mm or the defect depth exceeds 10% of the blank thickness), the blank is scrapped; the repaired part is tested again by flaw detection;
[0097] The cooled blank is placed in a dehydrogenation furnace, argon is filled into the dehydrogenation furnace, and the blank is heated to 1440°C for dehydrogenation treatment for 2.8 hours; after the dehydrogenation is completed, the blank is naturally cooled to room temperature with the furnace; a grinder is used to grind the alloy after the dehydrogenation treatment, and a reciprocating grinding method (repeated grinding back and forth) is used during the grinding; a polisher is used to polish the alloy after the grinding treatment, and the polishing temperature is controlled during the polishing process;
[0098] The alloy after dehydrogenation treatment was hot rolled at a temperature of 415°C and a time of 72 minutes; the alloy after hot rolling was cold rolled three times, cleaned and annealed; after the first cold rolling, it was annealed at 472°C for 68 minutes, and washed with dilute hydrochloric acid; after the second cold rolling, it was annealed at 782°C for 62 minutes; after the third cold rolling, it was annealed at 532°C for 62 minutes to obtain a Kovar alloy foil of target thickness; the foil after the third annealing was cleaned with an ultrasonic cleaner for 11 minutes and then polished.
[0099] Comparative Example 1
[0100] Prepare a raw material of Kovar alloy. The composition of the raw material of Kovar alloy is similar to that in the above embodiment, but the trace element S is not strictly controlled, and the mass percentage of S is 0.02% (higher than S≤0.01% in the embodiment); other main components are: C=0.012%, P=0.008%, Mn=0.38%, Si=0.18%, Cu=0.09%, Cr=0.09%, Mo=0.09%, Ni=28.9%, Co=17.1%, Zr=0.12%, Nb=0.08%, and the balance is Fe;
[0101] The Kovar alloy raw material is placed in an ordinary melting furnace for melting at a melting temperature of 1600°C, and a conventional nitrogen protective atmosphere is used; a general mold material is selected, and the inner surface of the mold is rough after grinding and polishing, and the surface roughness Ra is about 2μm; no special mold release agent is used, and pouring is directly performed; the metal liquid is only simply blown and degassed, and no vacuum treatment is performed; the pouring temperature is 1550°C, the pouring method is top pouring (different from the bottom pouring in the embodiment), and the pouring speed is fast, about 5-8kg / s; the mold has no heat preservation measures;
[0102] The surface was cleaned by simple mechanical grinding, and then directly tested without chemical cleaning. The flaw detection was carried out using only ultrasonic flaw detectors, with a fixed flaw detection frequency of 3MHz.
[0103] The blank was placed in a dehydrogenation furnace and dehydrogenated at 1400°C for 2.5 hours, during which argon gas was charged;
[0104] The hot rolling treatment temperature is 410°C, and the hot rolling time is 65 minutes; the cold rolling times are two times, and the annealing temperature after the first cold rolling is 450°C, and the annealing time is 50 minutes; the annealing temperature after the second cold rolling is 510°C, and the annealing time is 50-60 minutes; the third cold rolling and corresponding annealing treatment are not performed.
[0105] Comparative Example 2
[0106] Prepare a kovar alloy raw material, the composition of the kovar alloy raw material is calculated by mass percentage: C = 0.015%, P = 0.01%, S = 0.015% (slightly higher than the embodiment), Mn = 0.35%, Si = 0.20%, Cu = 0.10%, Cr = 0.10%, Mo = 0.10%, Ni = 28.8%, Co = 17.0%, Zr = 0.1%, Nb = 0.05%, and the balance is Fe;
[0107] The mold preparation is similar to that in the embodiment, but during the pouring process, the degassing treatment is not sufficient, and only a short blowing and stirring is performed, the argon flow rate is 4L / min, and the stirring time is 4 minutes; the pouring temperature is 1600°C, the pouring speed is 4.5kg / s, and the bottom pouring is adopted, but the thickness of the mold insulation layer is relatively thin, about 25mm;
[0108] In the heating process, the preheating temperature is 530℃, the holding time is 1.5 hours, the heating rate to the forging temperature is 90℃ / h, and the forging temperature is 1150℃; the deformation amount of each pass is between 20%, the rough forging passes are 3 times, and the fine forging passes are 4 times; the forging equipment is a small hydraulic press, and the pressure is controlled at 100MPa; after forging, air cooling is used for cooling, and the cooling speed is fast;
[0109] When cleaning the surface, the grinding pressure is 0.2MPa, the grinding speed is 10m / min, the chemical cleaning solution is dilute hydrochloric acid (concentration 7%), the amount of corrosion inhibitor added is 0.7% of the acid solution mass, the cleaning time is 13 minutes, and the stirring speed is 25r / min; in the flaw detection, the ultrasonic flaw detection frequency is 3.5MHz, the probe spacing is 60mm, the magnetic particle concentration is 15g / L, the magnetization current is 600A, and the magnetic field strength is 2500Gs;
[0110] The blank is placed in a dehydrogenation furnace, the dehydrogenation temperature is 1440°C, and the dehydrogenation time is 2.5 hours;
[0111] The hot rolling treatment temperature is 420°C and the hot rolling time is 65 minutes; the cold rolling is performed twice, and the annealing temperature after the first cold rolling is 470°C and the annealing time is 70 minutes; the annealing temperature after the second cold rolling is 770°C and the annealing time is 60 minutes; the third cold rolling and corresponding annealing treatment are not performed.
[0112] Comparative Example 3
[0113] Compared with the comparative example 2, the step of placing the blank into the dehydrogenation furnace for dehydrogenation is reduced, namely:
[0114] Prepare a kovar alloy raw material, the composition of the kovar alloy raw material is calculated by mass percentage: C = 0.015%, P = 0.01%, S = 0.015% (slightly higher than the embodiment), Mn = 0.35%, Si = 0.20%, Cu = 0.10%, Cr = 0.10%, Mo = 0.10%, Ni = 28.8%, Co = 17.0%, Zr = 0.1%, Nb = 0.05%, and the balance is Fe;
[0115] The mold preparation is similar to that in the embodiment, but during the pouring process, the degassing treatment is not sufficient, and only a short blowing and stirring is performed, the argon flow rate is 4L / min, and the stirring time is 4 minutes; the pouring temperature is 1600°C, the pouring speed is 4.5kg / s, and the bottom pouring is adopted, but the thickness of the mold insulation layer is relatively thin, about 25mm;
[0116] In the heating process, the preheating temperature is 530℃, the holding time is 1.5 hours, the heating rate to the forging temperature is 90℃ / h, and the forging temperature is 1150℃; the deformation amount of each pass is between 20%, the rough forging passes are 3 times, and the fine forging passes are 4 times; the forging equipment is a small hydraulic press, and the pressure is controlled at 100MPa; after forging, air cooling is used for cooling, and the cooling speed is fast;
[0117] When cleaning the surface, the grinding pressure is 0.2MPa, the grinding speed is 10m / min, the chemical cleaning solution is dilute hydrochloric acid (concentration 7%), the amount of corrosion inhibitor added is 0.7% of the acid solution mass, the cleaning time is 13 minutes, and the stirring speed is 25r / min; in the flaw detection, the ultrasonic flaw detection frequency is 3.5MHz, the probe spacing is 60mm, the magnetic particle concentration is 15g / L, the magnetization current is 600A, and the magnetic field strength is 2500Gs;
[0118] The hot rolling treatment temperature is 420°C and the hot rolling time is 65 minutes; the cold rolling is performed twice, and the annealing temperature after the first cold rolling is 470°C and the annealing time is 70 minutes; the annealing temperature after the second cold rolling is 770°C and the annealing time is 60 minutes; the third cold rolling and corresponding annealing treatment are not performed.
[0119] The hydrogen content (ppm), tensile strength (MPa), yield strength (MPa), elongation (%), hardness (HV), surface roughness (μm), and thickness uniformity (μm) of the Kovar alloy foils prepared in Examples 1 to 5 and Comparative Examples 1 to 3 are measured and performance parameters are compared.
[0120] Hydrogen content determination:
[0121] Using a LECORH-600 hydrogen analyzer, 1 g of sample was cut from the Kovar alloy foil prepared in each of the above embodiments and comparative examples, and the sample was cut into small pieces using a cutting tool to ensure that the sample could completely enter the reaction furnace of the analyzer, and the sample was placed in a clean and dry quartz boat; a sample with a standard hydrogen content (such as a Kovar alloy standard sample with a known hydrogen content) was used to calibrate the hydrogen analyzer, and according to the requirements of the instrument operation manual, the standard sample was placed in the instrument for measurement, and the instrument parameters were adjusted to make the measured value consistent with the known hydrogen content of the standard sample; the boat containing the sample was placed in the injection port of the hydrogen analyzer, and the instrument was started, and the instrument automatically sent the sample into the high-temperature reaction furnace, and the sample released hydrogen at high temperature; hydrogen entered the detection system along with the carrier gas, and the instrument recorded and calculated the hydrogen content, and displayed the measurement result in ppm (parts per million).
[0122] Tensile strength and yield strength determination:
[0123] Instron 5982 series electronic universal testing machine was used. According to the requirements of national standard GB / T228.1-2010 "Metallic Materials Tensile Test Part 1: Room Temperature Test Method", for Kovar alloy foil, dumbbell-shaped specimens were made, with a gauge length of 50 mm and a width of 10 mm (adjusted appropriately according to the actual thickness of the foil), and the thickness was the actual thickness of the foil; then the surface of the specimen was polished with sandpaper to remove the oxide layer and defects to ensure a smooth surface; the chuck spacing of the universal material testing machine was adjusted to a suitable position to adapt to the specimen length; the test speed was set to 3 mm / min; the force sensor and displacement sensor of the testing machine were turned on and cleared to ensure the accuracy of the initial data; the two ends of the specimen were clamped in the upper and lower chucks of the testing machine, respectively, to ensure that the specimen was clamped and perpendicular to the axis of the chuck; the testing machine was started and tension was applied; the testing machine automatically recorded the tension and elongation of the specimen and drew a stress-strain curve; when the specimen broke, the testing machine stopped loading and recorded the maximum tensile force value F at the time of fracture max , tensile strength σ b The calculation formula is: b =F max / A, where A is the original cross-sectional area of the specimen (A = width × thickness); for materials with obvious yielding, find the yield force F of the yield platform on the stress-strain curve y , yield strength σ y =F y / A; For materials without obvious yield phenomenon, the specified plastic elongation strength (such as Rp0.2, that is, the stress when the plastic elongation is 0.2%) is usually used as the yield strength, and the calculation is performed by finding the corresponding force value on the stress-strain curve.
[0124] Elongation determination:
[0125] Instron 5982 series electronic universal testing machine is used to measure the ratio of the gauge length elongation after the sample breaks to the original gauge length during the tensile test, which is the elongation. That is, during the tensile test for tensile strength determination, the gauge length elongation of the sample is recorded at the same time. After the sample breaks, the broken samples are butt-jointed together, and a measuring tool (such as a vernier caliper) is used to measure the total length L of the gauge length section after the break. f The calculation formula of elongation δ is: δ=(L f -L0) / L0×100%, where L0 is the original gauge length of the sample (here selected as 50 mm).
[0126] Hardness test:
[0127] Using MHV-1000Z automatic turret micro-Vickers hardness tester, cut the Kovar alloy foil into 10mm×10mm size specimens with the actual thickness of the foil; grind and polish the surface of the specimen to make it smooth and flat without oxide layer and scratches to ensure the accuracy of hardness measurement; set the test force of 0.4kgf (1kgf=9.8N); set the loading time and holding time of the hardness tester, the loading time is 15s, and the holding time is 15s; place the specimen on the workbench of the hardness tester, adjust the focal length, and make the indenter clearly align with the specimen surface; start the hardness tester, and the indenter is pressed into the specimen surface under the action of the test force, and the test force is removed after the specified time; use a microscope to measure the lengths d1 and d2 of the two diagonals of the indentation; the Vickers hardness value HV calculation formula is: HV=1.8544F / d 2 , where F is the test force (N), d = (d1 + d2) / 2 is the average length of the indentation diagonal (mm); the calculation result is averaged, 8 points are measured at different positions on the sample surface, and then the average value is taken as the hardness value of the sample.
[0128] Surface roughness measurement:
[0129] A Taylor-Hopson Surtronic S-128 surface roughness tester was used to cut a flat area of 50 mm × 50 mm from the Kovar alloy foil as the measurement sample; ensure that the sample surface is clean and free of dust, oil and other impurities to avoid affecting the measurement results. The surface roughness measuring instrument was calibrated using a standard roughness sample. The standard sample was placed on the measuring table and calibrated to make the instrument measurement value consistent with the known roughness value of the standard sample. The sample was placed flat on the measuring table and fixed to avoid movement during the measurement. The measuring probe was gently placed on the sample surface and the measuring instrument was started. The probe was scanned and measured on the sample surface at a certain speed and stroke. The instrument automatically recorded the measurement data and calculated the surface roughness parameters; 5 measurements were made at different positions on the sample surface, and the average value was taken as the surface roughness value of the foil.
[0130] Thickness uniformity measurement:
[0131] A German MahrMillimar C1208 thickness gauge was used, and a whole square Kovar alloy foil with a side length of 100 mm was selected as the measurement object to ensure that the foil was flat, without wrinkles and deformation; a measurement point was selected every 20 mm on the square foil with a side length of 100 mm, and a total of 25 points were selected; when using a micrometer screw, the micrometer screw was vertically contacted with the foil surface, and the differential cylinder was gently rotated so that the micrometer screw just contacted with the foil surface. After hearing a "click" sound, the value on the micrometer screw was read and recorded as the thickness value of the point; when using a thin film thickness gauge, the measuring probe was placed on the selected measuring point according to the instrument operating instructions, and the instrument automatically displayed the thickness value of the point, and the average thickness value of all measuring points was calculated. Calculate the thickness value t at each measuring point i With the average Deviation Thickness uniformity is measured by the maximum deviation max(|Δt i |) in μm; that is, thickness uniformity = max(|Δt i |), where i = 1, 2, ..., n, and n is the total number of measurement points.
[0132]
[0133] The various performance parameters measured by the above-mentioned Examples 1 to 5 and Comparative Examples 1 to 3 were compared and analyzed.
[0134] In terms of hydrogen content:
[0135] The hydrogen content of Examples 1 to 5 is in the range of 1.93-2.56ppm, which is at a relatively low level overall. This is due to the strict control of raw materials, smelting, pouring and other links during the preparation process. For example, argon protective atmosphere is used during smelting to prevent alloy oxidation and air inhalation. Sufficient degassing treatment is performed during the pouring process. For example, in Example 2, the molten metal is first kept in a vacuum environment of 30Pa for 12 minutes for preliminary vacuum treatment, and then argon gas is introduced for blowing and stirring, which effectively reduces the hydrogen content in the molten metal. The hydrogen contents of Comparative Examples 1 and 2 are 4.85ppm and 3.91ppm, respectively, which are significantly higher than those of the Example group. The control of trace element S in Example 1 is relatively loose (S=0.02%, higher than S≤0.01% in the embodiment), and the protective atmosphere and degassing measures during smelting and pouring are not as perfect as those in the embodiment, which may cause more hydrogen to enter the alloy; the process before the dehydrogenation step in Comparative Example 2 is also different from that in the embodiment, such as insufficient degassing treatment, resulting in a higher hydrogen content; Due to the lack of a dehydrogenation step in a dehydrogenation furnace, the hydrogen content in Comparative Example 3 is as high as 6.22ppm, the highest among all groups; this fully illustrates the importance of dehydrogenation treatment for reducing the hydrogen content of Kovar alloy foil. If dehydrogenation treatment is not carried out, a large amount of hydrogen will remain in the alloy, seriously affecting the material properties.
[0136] In terms of mechanical properties (tensile strength, yield strength, elongation):
[0137] Embodiments 1 to 5 show good performance in tensile strength, yield strength and elongation; the tensile strength is between 520-550MPa, the yield strength is between 480-505MPa, and the elongation is between 28%-35%; this is because a reasonable forging process is adopted in the preparation process, such as a multi-pass small deformation forging method (the deformation of each pass is controlled between 12%-18%), which gradually refines the organization and improves the mechanical properties of the material; at the same time, controlling the uniform atmosphere in the furnace during the heating process to prevent local oxidation or decarburization of the steel ingot also helps to improve the strength and toughness of the material; the tensile strength of comparative example 1 is 460MPa, the yield strength is 420MPa, and the elongation is 20%; the tensile strength of comparative example 2 is 485MPa, the yield strength is 440MPa, and the elongation is 23%; compared with the embodiment group, the mechanical The performance is obviously poor; this is mainly due to its deficiencies in raw material composition control, smelting and pouring process, forging process, etc.; for example, in comparative example 1, the internal surface treatment of the mold is rough, no special release agent is used, the pouring method is top-injection and there are no insulation measures, the heating rate is fast, the number of passes is small, the deformation is large, and the impact force and frequency of the equipment are unstable during the forging process, etc. These factors lead to uneven material structure and many defects, thereby reducing the mechanical properties; the mechanical properties of comparative example 3 are the worst, with a tensile strength of only 450MPa, a yield strength of 410MPa, and an elongation of 18%; in addition to the problems similar to those of comparative examples 1 and 2 in the preparation process, the lack of a dehydrogenation treatment step makes the hydrogen content in the material too high, and hydrogen will form defects such as hydrogen embrittlement inside the material, seriously weakening the mechanical properties of the material, resulting in a significant decrease in its tensile strength, yield strength and elongation.
[0138] In terms of hardness:
[0139] The hardness of Examples 1 to 5 is between 145-152HV, and the hardness value is relatively stable and within a reasonable range; this is because in the entire preparation process, from raw material selection to fine control of each process step, the uniformity and density of the material's organizational structure are guaranteed, so that the hardness performance is good; for example, in the process of blank processing, a combination of mechanical grinding and chemical cleaning is used to clean the surface, so as to prepare for subsequent flaw detection and processing procedures, and reduce the influence of surface defects on hardness measurement; at the same time, a reasonable heat treatment process (such as multiple cold rolling and annealing treatments) is also helpful to adjust the hardness of the material; the hardness of Comparative Examples 1 and 2 is 130HV and 135HV, respectively, which is lower than that of the embodiment group; the deficiencies in process control in the comparative examples, such as unstable smelting temperature, unreasonable forging process, etc., may lead to uneven organizational structure of the material, thereby affecting the hardness; the hardness of Comparative Example 3 is 125HV, which is the lowest among all groups; this is because it not only has the process problems of Comparative Examples 1 and 2, but also the high hydrogen content has a negative impact on the hardness of the material. Hydrogen will change the lattice structure of the material and reduce the hardness of the material.
[0140] In terms of surface roughness:
[0141] The surface roughness of Examples 1 to 5 is between 0.052-0.085 μm, and the surface quality is good. In the preparation process, attention is paid to the surface treatment of the mold and the use of the release agent, such as fine grinding and polishing of the inner surface of the mold, and the surface roughness Ra is controlled in a lower range. At the same time, a high-temperature resistant release agent is applied to the inner wall of the mold to reduce the adhesion between the steel ingot and the mold, and reduce the possibility of surface defects. In the subsequent processing process, such as polishing after cold rolling, the surface finish of the material is further improved. The surface roughness of Comparative Example 1 is 0.157 μm, and that of Comparative Example 2 is 0. .129μm, and comparative example three is 0.136μm, both higher than the embodiment group; the control of mold preparation, casting process and subsequent surface treatment in the comparative examples is not as strict as that in the embodiments; for example, the grinding and polishing treatment of the internal surface of the mold in comparative example one is relatively rough, which directly affects the surface quality of the steel ingot, and further leads to a higher surface roughness of the foil after subsequent processing; comparative examples two and three also have similar problems, and the differences in some process parameters (such as the concentration of the chemical cleaning solution and the amount of corrosion inhibitor added in comparative example two are different from those in the embodiments) may also affect the surface quality, resulting in a larger surface roughness.
[0142] In terms of thickness uniformity:
[0143] The thickness uniformity of Examples 1 to 5 is good, with a deviation between ±1.5-±3μm. During the rolling process, the uniform deformation of the material in the thickness direction is ensured by accurately controlling the hot rolling and cold rolling process parameters, such as the hot rolling temperature, time, number of cold rolling and annealing treatment. At the same time, the dimensional accuracy and organizational uniformity of the blank are effectively controlled during the blank processing and forging process, which provides a good foundation for subsequent rolling, thereby ensuring the thickness uniformity of the Kovar alloy foil. The thickness uniformity deviation of Comparative Example 1 is ±6μm, The comparative example 2 is ±5μm, and the comparative example 3 is ±6.5μm, which are obviously inferior to the embodiment group; the deficiencies in the rolling process and the early billet processing of the comparative examples lead to poor thickness uniformity; for example, the forging process control in comparative example 1 is not strict, and the mold has no insulation measures, etc., which may make the internal structure of the billet uneven, and large thickness deviations are likely to occur during rolling; comparative examples 2 and 3 also have similar process problems, and comparative example 3 lacks dehydrogenation treatment, so the material properties are more affected, and it is more difficult to ensure the uniformity of thickness during rolling.
[0144] It should be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, commodity or device. In the absence of further restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the process, method, commodity or device including the elements.
[0145] Each embodiment of the present invention is described in a progressive manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.
[0146] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present disclosure is limited to these examples. Based on the concept of the present disclosure, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of different aspects of one or more embodiments of the present invention as described above, which are not provided in detail for the sake of simplicity.
[0147] While the disclosure has been described in conjunction with specific embodiments thereof, many alternatives, modifications and variations of these embodiments will be apparent to those skilled in the art in light of the foregoing description.
[0148] One or more embodiments of the present invention are intended to cover all such replacements, modifications and variations that fall within the scope of protection of the present invention. Therefore, any omissions, modifications, equivalent replacements, improvements, etc. made within the spirit and principles of one or more embodiments of the present invention should be included in the scope of protection of this disclosure.
Claims
1. A method for preparing a kovar alloy foil, characterized in that: The preparation method comprises: S1: placing a kovar alloy raw material in a smelting furnace for smelting, and pouring the smelted molten metal into a target mold to form a steel ingot, wherein the mass percentage of the trace element S component in the kovar alloy raw material is controlled to be: S≤0.01%; S2: heating the steel ingot prepared in step S1 and forging it into a blank; S3: Cooling the blank forged in step S2 and then cleaning its surface; S4: performing a dehydrogenation treatment on the blank after the surface cleaning in step S3; S5: The alloy after the dehydrogenation treatment in step S4 is subjected to one hot rolling treatment and multiple cold rolling treatments to obtain a Kovar alloy foil of target thickness.
2. The method for preparing the Kovar alloy foil according to claim 1, characterized in that: The components of the Kovar alloy raw material include, by mass percentage: C≤0.015%, P≤0.01%, S≤0.01%, Mn: 0.35-0.45%, Si≤0.20%, Cu≤0.10%, Cr≤0.10%, Mo≤0.10%, Ni: 28.8%-29.2%, Co: 17.0-17.3%, Zr: 0.1-0.2%, Nb: 0.05-0.15%, and the balance is Fe.
3. The method for preparing the Kovar alloy foil according to claim 2, characterized in that: In step S1, the melting temperature is 1600-1700°C, and the melting is carried out under an argon protective atmosphere; before pouring, the molten metal is kept in a vacuum environment of 10-50Pa for 10-15 minutes for preliminary vacuum treatment, and then argon is introduced into the molten metal for blowing and stirring. The argon flow rate is controlled at 5-10L / min, and the stirring time is 5-8 minutes; the pouring temperature is 1550-1600°C, and the pouring speed is 2-5kg / s; the target mold is insulated during the pouring process.
4. The method for preparing the Kovar alloy foil according to claim 1, characterized in that: Step S2 specifically includes: The steel ingot prepared in step S1 is heated, firstly the steel ingot is heated to 550-600°C at a heating rate of 60-80°C / h for preheating, and the heat preservation time is 2-3 hours, and then the temperature is increased to a forging temperature range of 1150-1200°C at a rate of 100-120°C / h, and during the heating process, the oxygen content in the furnace is controlled to be below 0.05% by a gas circulation device in the furnace; The steel ingot is gradually forged into the required billet shape by using a multi-pass forging method with small deformation, and the deformation of each pass is controlled between 12% and 18%.
5. The method for preparing the Kovar alloy foil according to claim 4, characterized in that: Step S3 specifically includes: Place the blank in a holding furnace and slowly cool it down with the furnace at a cooling rate of 60-80℃ / h; The blank is polished by mechanical polishing, the polishing pressure is 0.2-0.4MPa, and the polishing speed is 10-15m / min; The blank is placed in a chemical cleaning tank and cleaned with a cleaning solution for 15-25 minutes. During the cleaning process, the cleaning solution is stirred at a stirring speed of 30-50 r / min. After cleaning, the blank is rinsed with clean water at a flushing pressure of 0.1-0.3MPa and a flushing time of 3-5 minutes.
6. The method for preparing the Kovar alloy foil according to claim 1, characterized in that: Step S4 specifically includes: Placing the blank after surface cleaning in step S3 in a dehydrogenation furnace, and filling the dehydrogenation furnace with argon gas; The alloy is heated and dehydrogenated in a dehydrogenation furnace, the dehydrogenation temperature is 1430-1480° C., and the dehydrogenation time is 2.5-3.5 hours; After dehydrogenation is completed, the dehydrogenation furnace is turned off and the alloy is allowed to cool naturally to room temperature in the dehydrogenation furnace.
7. The method for preparing the Kovar alloy foil according to claim 6, characterized in that: Step S4 also includes: The alloy after dehydrogenation treatment is ground by a grinding machine, wherein the grinding direction remains unchanged; The polishing machine is used to polish the alloy after grinding.
8. The method for preparing the Kovar alloy foil according to claim 1, characterized in that: Step S5 specifically includes: The alloy after the dehydrogenation treatment in step S4 is hot rolled at a temperature of 410-430° C. for 70-80 minutes; The hot-rolled alloy is subjected to multiple cold rolling, cleaning and annealing steps, wherein the annealing temperature after the first cold rolling is 470-480° C., the annealing time is 65-75 minutes, and the cleaning is carried out with dilute hydrochloric acid.
9. The method for preparing the Kovar alloy foil according to claim 8, characterized in that: The hot rolled alloy is subjected to three cold rolling, cleaning and annealing steps, specifically: The hot-rolled alloy is sent to a rolling mill for the first rolling, and the rolled alloy is washed with dilute hydrochloric acid and then annealed for the first time; The alloy after the first annealing is sent to a rolling mill for a second rolling, and the rolled alloy is washed with dilute hydrochloric acid and then annealed for a second time, wherein the annealing temperature is 780-790°C and the annealing time is 60-70 minutes; The alloy after the second annealing is sent to the rolling mill for the third rolling. The rolled alloy is washed with dilute hydrochloric acid and then annealed for the third time to obtain a Kovar alloy foil of target thickness, wherein the annealing temperature is 530-540°C and the annealing time is 60-70 minutes.
10. The method for preparing the Kovar alloy foil according to claim 9, characterized in that: Step S5 also includes: The Kovar alloy foil after the third annealing is cleaned with an ultrasonic cleaner for 10-15 minutes and then polished.
Citation Information
Patent Citations
Treatment process of low-temperature-resistant titanium alloy turbine blade
CN106435422A
Steel, product created from said steel, and manufacturing method thereof
CN108138286A
Extremely-thick high-strength high-compactness steel plate capable of being used for manufacturing large-sized structural components and manufacturing method thereof
CN108286020A
Constant-expansion alloy plate with good plasticity and preparation method thereof
CN115029641A
Fe-ni-co alloy ribbon for press-formed flat mask
JP2003073780A